Mechanism Controlling High‐Temperature Degradation of Sunflower Oil Triacylglycerols in the Absence of Oxygen. Issue 3 (23rd November 2020) - Kyselka, Jan; Cihelková, Klára; Lopes‐Lutz, Daise; Chudoba, Josef; Váchalová, Tereza; Alishevich, Katsiaryna; Hrádková, Iveta; Berčíková, Markéta; Mikolášková, Monika; Filip, Vladimír
Abstract: The aim of the present study is to describe the mechanism controlling heat‐induced formation of sunflower oil triacylglycerol and fatty acid methyl ester oligomers. The unique combination of high‐performance size‐exclusion chromatography with hyphenated electrospray ionization mass spectrometry (MS), atmospheric pressure chemical ionization‐MS, and high‐temperature gas chromatography‐MS techniques allows differentiating between radical coupling species and Diels–Alder cycloadducts. Targeted analysis of thermally degraded sunflower oils confirms the exact structures of various acyclic oligomers accompanied by less‐abundant products of pericyclic transformations. A series of model experiments simulate the impact of dienophile nature on the course of Diels–Alder reactions. Thus, α‐tocopherylquinone, δ‐tocopherylquinone, and methyl‐( E )‐11‐oxoundec‐9‐enoate are synthesized as naturally occurring dienophiles bearing electron‐withdrawing groups. The geometry of poor dienophiles does not affect concerted cyclization, while the structure of electron deficient dienophiles can overcome low reactivity. Practical Application : In the absence of oxygen, heat‐induced degradation of polyunsaturated triacylglycerols proceed predominantly via a radical pathway, whereas concerted reactions represent minor mechanisms. Sunflower oil triacylglycerol molecules in the system without propagation stage can be effectively protected by natural and/or synthetic antioxidants. Application of chelates is also recommended. However, antioxidant‐derived quinones, such as α‐tocopherylquinone, can enter the Diels–Alder reaction even more easily than dienophiles without electron‐withdrawing groups. Unsaturated core aldehydes possess the same reactivity. Examination of the mechanism controlling high‐temperature degradation of triacylglycerols is especially important for processing engineers in edible oil refineries and food technologists. New perspective may help them to minimize undesirable changes in polyunsaturated species. Abstract : This study investigates the mechanism controlling heat‐induced formation of sunflower oil triacylglycerol oligomers. The unique combination of preparative high‐performance size‐exclusion chromatography with hyphenated mass spectrometry techniques confirms major radical coupling species accompanied by Diels–Alder cycloadducts. Quinones and unsaturated core aldehydes represent naturally occurring dienophiles that can enter the Diels–Alder reaction more easily.